SISTEM PAKAR DIAGNOSA HAMA DAN PENYAKIT TANAMAN CABAI BESAR MENGGUNAKAN METODE CERTAINTY FACTOR - Tomi Winanto, Yustina Retno Wahyu Utami, Sri Hariyati Fitriasih (STMIK Sinar Nusantara, 2017)
Chili plants have a lot of pest and disease attacks. Pest and disease attacks potentially reduce the production of chilli and even cause crop failure. In addition, the limited number of extension workers and the lack of knowledge of practitioners / chili farmers inhibits efforts to control pests and diseases of chili plants. Therefore, the authors propose an expert system to diagnose pests and diseases in large chili plants using the Certainty Factor method. The Certainty Factor method is used to perform calculations by providing an expert's level of confidence. Expert systems relate symptoms and diseases as well as pest and disease control solutions of large chili plants. The data were obtained based on interviews with experts at the Organization for Industrial, Spiritual and Cultural Advancement (OISCA) Training Center Karanganyar. The data obtained was analyzed and expert system design application was made using UML diagram. The design is continued with the implementation of expert system application into PHP programming and MySQL database. The test results show that the system can diagnose pests and diseases of large chili plants like an expert. Keyword: certainty factor, expert system, pest and disease, large chili plant (Capsicum Annuum Longum).